The Feasibility of Developing a Repository of Assessments of Hard-to-Measure Competencies - Yuan, Kun (RAND Corporation, 2015)
This report explores the feasibility of and challenges associated with building a repository of assessments of hard-to-measure competencies. The authors examined the procedures needed to collect, review, document, and catalog assessments for a computerized database. The authors also examined web-based archives to identify the best functional modules and user-interface features to incorporate into a repository of measures.